Technology Talk: Public Speaking Textbooks' Coverage of Information Retrieval Technology Systems. - Child, Jeffrey T.; Pearson, Judy C.; Amundson, Najla G. (Communication Quarterly, 2007)
College students use technology to gather information and conduct their daily lives. Textbooks increasingly relate course content to students through technology. An analysis of the top ten public speaking textbooks revealed the ways in which technology is addressed within information-gathering chapters. Seven areas of technology were identified: search engines / conducting searches, the Internet, general computing, non-computer technologies, technology applications, technology in general, and the provision of Website addresses. Chi-square tests showed significant differences in the coverage of the technology topics. Instructors can make more informed textbook selections as a result of this investigation. Technology is essential to the information gathering process, and this study suggests how its treatment may be more beneficial to both students and instructors. Reprinted by permission of the publisher.